Antioxidant Activity And Phenolic Compounds Contents Of Spider Flower (Cleome Arabica Ssp.Arabica), A Well Acclimated Species In The Algerian Desert Areas - Aicha, Madi; Nadia, Zaghed; Sihem, Halmi; Abdelmalik, Belkhiri (European Scientific Journal, ESJ, 2017)
A detailed study was performed on the antioxidant activity of the alcoholic extract of different plant parts of Cleome Arabica ssp. arabica (CAA) in relation with their total phenolic, flavonoid and proanthocyanidins contents in order to find possible sources for future novel antioxidants in food and pharmaceutical formulations. The total yield, total phenolic (TP), total flavonoids (TF) and total proanthocyanidins (TPA) contents of all the fractions were also determined. Cleome Arabica ssp. arabica was also subjected to preliminary phytochemical screening test for various constituents. The total phenolic contents (TPC) of three parts (Leaves, seeds and roots) was 78,56 ± 0,01 mg GAEq/g extract, while total flavonoid contents (TFC) of the same parts was 19,57 ± 0,01 mg REq/g extract, and total proanthocyanidins (TPA) was 17,41 ± 0,01 mg CYEq/ g of extract. Leaves extract was found significantly higher as compared to other parts extracts. Phytochemical screening of leaves, seeds and roots extracts revealed the presence of alkaloids, coumarins, flavonoids, saponins, tannins and terpenoids. The antioxidant capacity of extracts was determined by three methods DPPH, FRAP, and phosphomolybdenum. The obtained results showed that leaves extract has the highest antioxidant capacity with low value of IC50 for DPPH and FRAP and the highest quantity of antioxydants compounds in phosphomolybdenum assay, followed by seeds extract and finally roots extract.